Brazilian footballers and the self-report of medicine intake: The show must go on - André Valentim Siqueira Rodrigues; Elisa Suzana Carneiro Pôças; Henrique Marcelo Gualberto Pereira; Bruna de Jesus Labanca; Felipe Alves Gomes de Oliveira; Sandra Celina Fernandes Fonseca; Victor Manuel Machado de Ribeiro dos Reis; Eduardo Camillo Martinez (Motricidade, 2025)
Athletes, especially footballers, frequently use non-steroidal anti-inflammatory drugs (NSAIDs) and other medications. However, limited research on prolonged usage exists, particularly among Brazilian athletes. This study aims to investigate the prevalence of NSAIDs and analgesics in Brazilian footballers, comparing their use with that of athletes from Olympic and Paralympic sports, considering sex, competition period (in or out-of-competition), and sport type (contact or non-contact). An observational study analyzed 8,997 Doping Control Forms from 2021 and 2022, managed by the Brazilian National Anti-Doping Organization. Data such as sport, sex, collection period, and self-reported medication use in the preceding week were extracted. Medications were categorized into five groups: no medication, non-selective NSAIDs, selective NSAIDs (Cox-2), analgesics/myorelaxants, and paracetamol/dipyrone. χ2 tests compared athlete groups, medication use, sex, sport, and test period at a 95% significance level. Results showed higher NSAID usage among footballers compared to Olympic and Paralympic athletes and athletes in contact and non-contact sports. In-competition periods were a significant factor, with footballers showing increased NSAID use compared to other athletes.